Impact of a Stroke Recovery Program Integrating Modified Cardiac Rehabilitation on All-Cause Mortality, Cardiovascular Performance and Functional Performance. (November 2019) - Cuccurullo, Sara J.; Fleming, Talya K.; Kostis, William J.; Greiss, Christine; Gizzi, Martin S.; Eckert, Anne; Ray, Arlen Razon; Scarpati, Rosann; Cosgrove, Nora M.; Beavers, Traymon; Cabrera, Javier; Sargsyan, Davit; et al.
Abstract : Objective: Using a feasibility analysis and matched subgroup analysis, this study investigated the implementation/safety/outcomes of a stroke recovery program (SRP) integrating modified cardiac rehabilitation for stroke survivors. Design: This prospective cohort study of 783 stroke survivors were discharged from an inpatient rehabilitation facility to an outpatient setting; 136 SRP-participants completed a feasibility study and received the SRP including modified cardiac rehabilitation, 473 chose standard of care rehabilitation (nonparticipants), and a group ( n = 174) were excluded. The feasibility study assessed the following: safety/mortality/pre-post cardiovascular performance/pre-post function/patient/staff perspective. In addition to the feasibility study, a nonrandomized subgroup analysis compared SRP-participants ( n = 76) to matched pairs of nonparticipants ( n = 66, with 10 nonparticipants used more than once) for mortality/pre-post function. Results: The feasibility study showed the SRP to have the following ( a ) excellent safety, ( b ) markedly low 1-yr poststroke mortality from hospital admission (1.47%) compared with national rate of 31%, ( c ) improved cardiovascular performance over 36 sessions (103% increase in metabolic equivalent of tasks times minutes), ( d ) improved function in Activity Measure of Post-Acute Care domains ( P < 0.001), ( e ) positive reviews from SRP-participants/staff. Subgroup analysis showed the SRP to ( a ) positively impact mortality, nonparticipants had a 9.09 times higher hazard of mortality ( P = 0.039), and ( b ) improve function in Activity Measure of Post-Acute Care domains ( P < 0.001). Conclusions: Stroke survivors receiving a SRP integrating modified cardiac rehabilitation may potentially benefit from reductions in all-cause mortality and improvements in cardiovascular performance and function.